Robotics: Science and Systems XV 2019
DOI: 10.15607/rss.2019.xv.081
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Autonomous Robot Teleoperation with Obstacle Avoidance Via Model Predictive Control

Abstract: This paper 1 proposes a model predictive control approach for semi-autonomous teleoperation of robot manipulators: the focus is on avoiding obstacles with the whole robot frame, while exploiting predictions of the operator's motion. The hand pose of the human operator provides the reference for the end effector, and the robot motion is continuously replanned in real time, satisfying several constraints. An experimental case study is described regarding the design and testing of the described framework on a UR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Besides, SC can be designed to improve the user's ability to remotely operate complex machines while simultaneously avoiding unsafe regions [43]: to this end, obstacles avoidance can be performed by autonomously overriding the user's commands leveraging reactive techniques such as artificial potentials fields [16] or model predictive control [44].…”
Section: B Remote Interactionmentioning
confidence: 99%
“…Besides, SC can be designed to improve the user's ability to remotely operate complex machines while simultaneously avoiding unsafe regions [43]: to this end, obstacles avoidance can be performed by autonomously overriding the user's commands leveraging reactive techniques such as artificial potentials fields [16] or model predictive control [44].…”
Section: B Remote Interactionmentioning
confidence: 99%
“…Based on the linear relationship on the robot link speed, Zanchettin et al [21] derived a set of inequalities to determine whether a certain point in the collaborative workspace is safe and visualized the danger filed generated by the robot. Rubagotti et al [22] investigated a predictive model for obstacle-avoidance robot teleoperation.…”
Section: Safe Hrc Manufacturing Systemmentioning
confidence: 99%
“…The UR5 robot was equipped with a Robotiq 3-finger adaptive gripper (www.robotiq.com/products/industrial-robot-hand) and controlled using a newly formulated nonlinear model predictive control (NMPC) system that allowed the manipulator end-effector to track the operator's wrist pose in real time and, at the same time satisfying joint velocity and acceleration limits, avoiding singular configurations and workspace constraints, including obstacles. The detailed formulation of the NMPC control framework and its implementation for the case study of the UR5 robot semi-autonomous teleoperation with obstacle avoidance is reported in [31]. The gripper control was realized using a low-cost force sensitive resistor sensor attached to the operator's glove and interfaced with the wrist IMU sensor module of the system prototype for sensor signal transmission to a control PC, via the module's integrated Wixel communication board.…”
Section: System Application In Robotics Researchmentioning
confidence: 99%
“…Evolution of the arm motion-tracking system designs: (a) the 4-DOF system (Phase 1)[22]; (b,c) the 7-DOF double-arm system used in[30] (Phase 2); (d) the final 7-DOF system (Phase 3) used in[31].…”
mentioning
confidence: 99%